Comparison of feeding systems for finishing swine - J Vargas Vargas; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1984)
Two feeding trials using 240 finishing pigs were conducted to evaluate meal feeding and ad libitum dry and wet feeding. Growth rate was significantly improved by wet feeding in trial 1. Overall, a 5% improvement in growth rate occurred by wet feeding in both trials when compared with meal-feeding or ad libitum dry feeding. Feed efficiency was similar for pigs fed meals, and ad libitum dry or wet diets.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Feeding systems; Finishing pigs